Dampak Talent Management terhadap Employee Retention pada Millenials Workforce - Sumarni, Murti (Universitas PGRI Yogyakarta, 2018)
The aim of this research was focused to determine the impact of Talent Management to Employee Retention in the case of Millenials Workforce. Previous research found that Human Resource Development Manager were dealing with Y Generation who had a unique work ethic, so it needed a different retention of employee. The reliability and validity test was conducted to 30 respondents and the result showed that all questions item were proven valid and reliable to be used in further research analysis. Populations in this research were the millennial employees. Questionnaire was used to collect the data in the amount of 60 respondents. This research used SPSS to analyze and the result of the linier regression analysis indicated that the Talent Management had a significant effect to Millenials Workforce Employee Retention.Keyword: Talent Management, Millenials Workforce, Employee Retention